A Comparative Study On Quality of Life Between Thrombolysed and Non-Thrombolysed Ischemic Stroke Patients: Pharmaceutical Science-Pharm-D - Vankodoth Sireesha, Dr.; Sushma, V.; Bhavitha Naga Sai, K.; Sana, Sumaiya; Pratibha, M.; Sunil Kumar, M.; kanna reddy, chintalapally (International Journal of Life Science and Pharma Research, 2023)
Stroke is one of the leading causes of morbidity and mortality worldwide. Ischemic strokes are the most common variety of strokes caused by either thrombosis or embolism. In addition, they account for 50% – 85% of cerebrovascular accidents. Thrombolysis is used in the treatment of acute ischemic stroke. The current study examined the clinical profile and assessed risk factors, adverse events, and quality of life between thrombolytic and non-thrombotic ischemic stroke patients. A prospective observational study was conducted in a tertiary care Hospital with a sample size of 106 Ischemic stroke patients for four months. The patients were enrolled based on inclusion and exclusion criteria and were interviewed using a semi-structured questionnaire. Quality of life was assessed using Stroke specific quality of life scale (SSQOL). The results showed that the incidence of stroke is most common in the age group of 61-80 years, with a mean age of 59.9 years. Hypertension was the leading risk factor in 74.4% of cases. Speech Involvement (74.5%) was the most common presentation, followed by Hemiparesis, Altered sensorium. In our study, patients presenting to hospital >4.5hrs were higher, and the quality of life between thrombolysis and non-thrombolysis patients were nearly identical. However, there was applied statistically significant distinction in energy, mobility, self-care, vision, and work items of the SSQoL scale. We conclude that the two groups had no major variations within the primary outcome of QOL. Thus, the current study tends to expect that patients with non-thrombolytic therapy will have a worse quality of life due to the greater initial stroke severity. Therefore, medical care appears to be of more importance in achieving a higher quality of life in ischemic thrombolysis stroke patients who reply to this therapy.